Strategi Penguatan Kerja Sama Antar Daerah dalam Pengelolaan Transjatim untuk Transportasi Publik Berkelanjutan - Nia Putri Agung; Juwita Nur Fadila; Bunga Avrillia Putri (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study analyzes the mechanism of inter-regional cooperation in managing TransJatim as a sustainable public transportation system in East Java. Using a qualitative approach and literature study, the study identified three main aspects: (1) a multi-level collaboration model between the provincial government and five regencies/cities (Surabaya, Gresik, Mojokerto, Lamongan, Bangkalan) regulated through Governor Regulation No. 15/2018 and inter-regional MoU; (2) four main obstacles including policy asymmetry, fiscal inequality, technological disparity, and local political dynamics; and (3) strengthening strategies through five pillars: institutional consolidation, regulatory harmonization, financing strengthening, digital transformation, and capacity building. The findings show that the effectiveness of current collaboration is hampered by the lack of an authorized joint management institution and a clear accountability system. The study recommends the establishment of an independent TransJatim Management Agency, the preparation of integrated SOPs, a sustainable financing system, and an integrated digital platform to support the achievement of SDGs (especially goals 11 and 13) in sustainable transportation. The strategy implementation is proposed in three stages: preparation (1 year), transition (2 years), and full operation.